Iron Status Assessment in Chronic Kidney Disease Patients Preceding Dialysis: An Exploration of Anemia and Iron Deficiency - Aqsa Naeem, Nouman Zahid, Fahad Nauman Safir, Adeel Anwar, Abdul Karim Soomro, Zahwa Alyas, Khurram Shahzad (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The most common kind of anemia, iron deficiency anemia (IDA), is very burdensome for those with chronic kidney disease (CKD). The incidence of IDA rises as renal function deteriorates. The incidence of IDA in CKD patients before the need for dialysis has not been well documented in Pakistan, even though the major cause of anemia in CKD individuals is a shortage of erythrocyte a hormone generated by the kidneys that stimulates red blood cell synthesis. This study’s goal is to identify the incidence of IDA in people with kidney failure who are still not receiving dialysis. Methods: We included 188 pre-dialysis CKD patients, ages 18 to 75, of both sexes. Patients with apparent anemia-related reasons were eliminated. During OPD follow-up, it was then established what proportion of patients had IDA in their pre-dialysis CKD. Results: The patients who participated in the research had an average age of 46.03 years, with a standard deviation of 12.24 years. There were 188 patients in all, and 102 of them were men, making up around 54.26% of the sample. The study’s 1.2 to 1 male-to-female ratio indicates that men were overrepresented. 73 people, or around 38.83% of the total patients in the research, were found to have iron deficiency anemia (IDA) among people with chronic kidney disease (CKD) who had not yet begun dialysis. Practical Implication: The causes of iron shortage in those with CKD are complicated by several variables, chief among them being decreased nutritional iron consumption and poor gastrointestinal absorption of iron, blood losses brought on by uremia-induced platelet disorder, and persistent inflammation related to CKD. As a result, owing to chronic inflammation causing a reactive rise in ferritin, individuals with CKD have much higher ferritin threshold levels for the absolute iron shortage. As a result, it is advised that patients with CKD before starting dialysis have blood ferritin levels below 100 µg/ml and over 200 µg/ml for those who are already receiving it Conclusions: According to the study, IDA occurs often in pre-dialysis CKD patients. By paying strict attention to the sources of IDA and replacing it, patients’ outcomes may be improved. Keywords: anemia, dialysis, chronic kidney disease, erythrocyte, iron deficiency, hormone